Unnatural causes [videorecording (DVD)] - James, P. D.; Marsden, Roy, 1941-; Nighy, Bill, 1949-; Martin, Mel, 1947-; James, P. D. (P.D. James the essential collection, 2008)
"Dalgliesh is drawn into an increasingly troubling murder case and a multi-million dollar currency scam"--Koch Entertainment booklet.